Queensland government gazette : extraordinary vol. CIX, no. 213 - Queensland; Ryan, T. J. (Thomas Joseph), 1876-1921; Cumming, Anthony J. (Brisbane : A. J. Cumming, Govt. Printer, 1917)
The censor's office forbade the publishing of the debate on the question of military censorship which took place on 22 November 1917. When queried by the Government Printer, no reply was received but a raid was carried out by military authorities on the Queensland Government Printing Office and several thousand copies of Hansard were seized. Subsequently, the Premier, T. J. Ryan wrote to the Prime Minister to protest and to request the postal authorities transmit the copies of Hansard in their possession and the military authorities return the seized copies. He pointed out that the Prime Minister had earlier stated the censor had no power to censor the official reports of any of the states. No reply was received.
"Published by authority".
"To the public of Queensland, I deem it my duty on behalf of the Government of Queensland, a sovereign State of the Commonwealth of Australia, to inform you that "Hansard", no. 37, containing a report of the proceedings of the Legislative Assembly of this State on the 22nd instant, had been denied transmission through the Post Office by the Federal Government..."
Also available online
Keywords: World War, 1914-1918 -- Censorship -- Australia; Gazettes -- Queensland; Australian